2005
DOI: 10.1055/s-2005-870155
|View full text |Cite
|
Sign up to set email alerts
|

Endoanal Ultrasound-Guided Surgery for Anal Fistula

Abstract: These data highlight the diagnostic accuracy of EAUS, particularly when hydrogen peroxide injection or 3-D imaging are used. Basing our surgical decision making on EAUS findings allowed us to carry out curative operations in a significantly large number of patients; the recurrence rate was very low. The accurate EAUS assessment of the relationship between fistulas and sphincters has been the main factor in choosing a sphincter-saving surgical procedure, avoiding fecal incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
58
1
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 16 publications
11
58
1
6
Order By: Relevance
“…In the present study, the agreement of 3D-EAUS with surgery was excellent: 84% in the detection of primary tracts, 84% in internal openings, and 82% in secondary extensions. These outcomes are consistent with recent data concerning 3D-EAUS [16][17][18] . Most reports using conventional 2D-EAUS have shown superior results with H2O2 enhancement.…”
Section: Kim Y Et Al Endoanal Ultrasound In Anal Fistulasupporting
confidence: 82%
See 1 more Smart Citation
“…In the present study, the agreement of 3D-EAUS with surgery was excellent: 84% in the detection of primary tracts, 84% in internal openings, and 82% in secondary extensions. These outcomes are consistent with recent data concerning 3D-EAUS [16][17][18] . Most reports using conventional 2D-EAUS have shown superior results with H2O2 enhancement.…”
Section: Kim Y Et Al Endoanal Ultrasound In Anal Fistulasupporting
confidence: 82%
“…However, only a few reports have addressed the effect of H2O2 in 3D-EAUS. Ratto et al [16] obtained improved diagnostic accuracy by using H2O2, and West et al [5] reported high diagnostic accuracy with H2O2 enhanced 3D-EAUS, comparable to MRI. However, the improved accuracy was not apparent in the study of Buchanan et al [17] .…”
Section: Kim Y Et Al Endoanal Ultrasound In Anal Fistulamentioning
confidence: 99%
“…Agreement between ERUS and EUA according to kappa was classified as perfect (k=1), very good (k=0.81-0.99); good (k=0.61-0.80), moderate (k=0.41-0.60), fair (k=0.21-0.40), and poor (k=0.20 or less) [17]. Sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of MRI fistulography were calculated.…”
Section: Discussionmentioning
confidence: 99%
“…Gleiches gilt für andere technische Untersuchungsmög-lichkeiten wie Fistulographie, Computertomographie und Magnetresonanztomographie [21,22]. Zur Vermeidung von Rezidiven in der Fistelchirurgie wird dem EAUS in der präoperativen Diagnostik ein hoher Stellenwert zur konkreteren Therapie-und Operationsplanung zugeschrieben [23,24]. Abbildung 4.…”
Section: Diskussionunclassified